2019
DOI: 10.1111/joop.12294
|View full text |Cite
|
Sign up to set email alerts
|

Social identity management strategies of women in STEM fields

Abstract: Recruiting and retaining women in science, technology, engineering, and mathematics (STEM) occupations is seen as challenging, and researchers have begun to consider how women manage their identity in these contexts in response to potential questions of fit. Within identity management theoretical work, there has been little attention to occupational influences. Based on role congruity theory, we investigate occupational characteristics as influences on women's gender identity management, along with individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Prior convergent validity evidence suggests process orientation is related to other conscientiousness scales (e.g., r = .63 with NEO conscientiousness), with emotive orientation having more modest relationships with measures of emotional stability/neuroticism (−.30 and .23 with 16PF stability and NEO neuroticism scales) (see Birkman et al, 2013). Corrected correlations (for attenuation due to unreliability) between emotive orientation and NEO neuroticism have been reported as .25, and between process orientation and NEO conscientiousness as .81 (Birkman, Elizondo, Lee, Wadlington, & Zamzow, 2008; Ryan, King, Elizondo, & Wadlington, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Prior convergent validity evidence suggests process orientation is related to other conscientiousness scales (e.g., r = .63 with NEO conscientiousness), with emotive orientation having more modest relationships with measures of emotional stability/neuroticism (−.30 and .23 with 16PF stability and NEO neuroticism scales) (see Birkman et al, 2013). Corrected correlations (for attenuation due to unreliability) between emotive orientation and NEO neuroticism have been reported as .25, and between process orientation and NEO conscientiousness as .81 (Birkman, Elizondo, Lee, Wadlington, & Zamzow, 2008; Ryan, King, Elizondo, & Wadlington, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Women in STEM who perceive a lack of fit engage more in practices such as downplaying their social category or highlighting positive features of their gender identity (Ryan et al, 2020). However, these women engage less in these practices when they feel supported by the organization (Ryan et al, 2020) and are also more productive and satisfied in supportive climates (Settles et al, 2006). Due to circumstances associated with the COVID-19 pandemic, workers faced dramatic changes in their work and nonwork demands and lacked access to their previous supports.…”
Section: Boundary Management For Stem Womenmentioning
confidence: 99%
“…Because of perceptions that women do not belong in STEM fields, explained by role congruity theory (Eagly & Karau, 2002), many STEM women experience an inherent conflict between their gender and professional identities (Settles et al, 2009). Women in STEM who perceive a lack of fit engage more in practices such as downplaying their social category or highlighting positive features of their gender identity (Ryan et al, 2020). However, these women engage less in these practices when they feel supported by the organization (Ryan et al, 2020) and are also more productive and satisfied in supportive climates (Settles et al, 2006).…”
Section: Boundary Management For Stem Womenmentioning
confidence: 99%
“…Specific to coping behavior, POS has been linked to proactive strategies. For example, Ryan et al (2019) found that POS increased the likelihood that women in STEM would confront stigmatizing behaviors. They argue that this occurs because women with high POS may perceive they would be supported by the organization if they were to directly address discrimination.…”
Section: Methodsmentioning
confidence: 99%